Behavioural discrimination of solitary and gregarious phases of Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) - Barrios Rojas, Katty Elena (2015)
Anticarsia gemmatalis is a species of Lepidoptera characterized by the capacity to express differentially its genotype as part of adaptation strategies to environmental changes. This phenomenon is called phenotypic plasticity and is considered one of the main reasons for the evolutionary success. Phenotypes or "phases" described for larvae of Anticarsia gemmatalis are: solitary, gregarious and intermediary. These phases differ not only in morphological parameters but also in physiological, ecological and behavioural parameters. As regards the behaviour, many studies have confirmed that this is a basic component of phenotypic plasticity and the first to be expressed when there is a phase change. For Lepidoptera, although some clues are known, the factors that induce and maintain the phase change process have not been fully elucidated. Thus, the objectives of our study were to describe the behavioural repertoires of solitary and gregarious phases of Anticarsia gemmatalis and test if specific mechanical and/or chemical stimuli induce the phase change in this species. For the description of the behavioural repertoire were used 50 solitary and 50 gregarious phase larvae. In an experimental arena, each larva was observed for 780s in order to register the different components of its behaviour. For the induction of phase change, solitary phase larvae were selected and divided into groups in which stimuli were applied. To apply the mechanical stimulus 120 solitary larvae were selected and divided into 4 groups of 30 which were stimulated with a nylon thread on the head, on the third abdominal segment or on the last abdominal segment, according to the group. The control group remained without stimulation. To apply chemical stimulus 160 larvae were selected and divided into four groups of 40. For the three stimulus groups cuticular hydrocarbon extracts of Anticarsia gemmatalis solitary phase larvae, Anticarsia gemmatalis gregarious phase larvae and Spodoptera frugiperda larvae were used, according to the group. For the control group we applied the organic solvent used in the extraction of cuticular hydrocarbons. The selected larvae were exposed to cuticular hydrocarbons by allowing them to walk on a filter paper containing the extracts for 12 hours. For the first objective, the results indicated that there is a difference between the behaviours of Anticarsia gemmatalis solitary and gregarious phases. The solitary phase larvae are characterized by having a more sedentary behaviour and perform a larger number of head movements; meanwhile, gregarious phase larvae are characterized by being more active in the arena and by perform a greater number of walking events. Regarding the second objective, the results indicated that none of the treatments differed significantly (p <0.05), so none of the applied stimuli induced a phase change in this species. We believe that differences in behavioural patterns could be reflecting adaptive processes inherent to lifestyles of the phases and that these differences can have an impact on the biology, ecology and distribution strategies of Anticarsia gemmatalis.